Pengaruh Media Sosial dan Peran Keluarga terhadap Perilaku Seksual Remaja di Wilayah Kerja Puskesmas Kabil - Rahayu Putri, Mona; Abdul Hafid, Rachmawati; Dewi Haryati, Sri (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2021)
Free sex behavior is behavior that is driven by sexual desire, both with the opposite sex and with the same sex. The forms of this behavior usually vary, ranging from feelings of attraction to behavior dating, intercourse and making out. The research method is analytic observational with a cross sectional design. The sample size in this study was 100 adolescents. The results of the bivariate analysis carried out found that there was an effect of using social media on adolescent sexual behavior with a P value of 0.001 and there was an effect of using family support on adolescent sexual behavior with a P value of 0.003. Suggestions in this study are to provide counseling to adolescents about the use of social media and adolescent sexual behavior and provide counseling to families to always provide support to adolescents so that they can reduce the risk of sexual behavior.